2016
DOI: 10.1371/journal.pone.0156386
|View full text |Cite
|
Sign up to set email alerts
|

Low Health System Performance, Indigenous Status and Antivenom Underdosage Correlate with Spider Envenoming Severity in the Remote Brazilian Amazon

Abstract: BackgroundA better knowledge of the burden and risk factors associated with severity due to spider bites would lead to improved management with a reduction of sequelae usually seen for this neglected health problem, and would ensure proper use of antivenoms in remote localities in the Brazilian Amazon. The aim of this study was to analyze the profile of spider bites reported in the state of Amazonas in the Western Brazilian Amazon, and to investigate potential risk factors associated with severity of envenomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
2
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 49 publications
(74 reference statements)
2
12
2
7
Order By: Relevance
“…The mean of the morbidity coefficient (12 cases/100,000 inhabitants) during the period of this study was higher than that of some municipalities in the neighboring state of Amazonas (4 cases / 100,000 inhabitants) reported by Sampaio et al 6 and lower than in other municipalities, Rio Preto da Eva (91 cases/100,000 inhabitants) and Apuí (58 cases/100,000 inhabitants), also in Amazonas state. Incidents with scorpions had an average of 29.28 cases /100.00 inhabitants, being higher than that registered for the Amazonas state (7.6 cases/100,000 inhabitants), which presents higher incidence levels in two of its municipalities, Rio Preto da Eva (58.9 / 100,000 inhabitants) and Apuí (182.6 cases/100,000 inhabitants) 5 .…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…The mean of the morbidity coefficient (12 cases/100,000 inhabitants) during the period of this study was higher than that of some municipalities in the neighboring state of Amazonas (4 cases / 100,000 inhabitants) reported by Sampaio et al 6 and lower than in other municipalities, Rio Preto da Eva (91 cases/100,000 inhabitants) and Apuí (58 cases/100,000 inhabitants), also in Amazonas state. Incidents with scorpions had an average of 29.28 cases /100.00 inhabitants, being higher than that registered for the Amazonas state (7.6 cases/100,000 inhabitants), which presents higher incidence levels in two of its municipalities, Rio Preto da Eva (58.9 / 100,000 inhabitants) and Apuí (182.6 cases/100,000 inhabitants) 5 .…”
Section: Discussioncontrasting
confidence: 66%
“…The majority of cases reported were scorpion stings (164 cases, 70%), which is the most frequent at the national level 1,2 and also in studies conducted in other regions of the country 5,6,[11][12][13] . However, the mean incidence of cases of spider bites (12 cases) and scorpion stings (29.28) recorded per 100,000 inhabitants in this study for Cruzeiro do Sul is much higher than that reported for Brazil (2.9 and 16.7, respectively) and in the state of Acre (3.85 and 4.58) by Chippaux 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IDSUS -effectiveness also showed a negative association with the mean ACL rate, assuming a protective role. As previously reported in studies with tuberculosis and venomous animals [39,40], IDSUS -effectiveness estimates the degree to which services of primary care, outpatient care, and emergency services achieve the expected results [17]. If the IDSUS-effectiveness score increases, it is understood that health services and actions have achieved their goals thus reducing the probability of high ACL rates.…”
Section: Discussionmentioning
confidence: 98%
“…In the Brazilian Amazon region, the reporting of cases involving venomous animals is probably much lower than the actual number of cases, mainly due to the difficulty in traversing the riverine topography, and the indigenous populations arriving at the health centers 8 . Thus, this study aimed to analyze the profile of stings by insect in the order Hymenoptera (ants, bees, and wasps), reported in the state of Amazonas, and the spatial distribution thereof.…”
mentioning
confidence: 99%